Pengaruh Konservatisme Dan Investment Opportunity Set (IOS) Terhadap Kualitas Laba dengan Kepemilikan Manajerial Sebagai Pemoderasi - Yunita, Putu Astri; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p10, 2018)
This study examines the influence of conservatism and investment opportunity set (IOS) on earnings quality with managerial ownership as a moderating variable in manufacturing firms listed on the Indonesia Stock Exchange. The purpose of this study is to determine (1) the influence of conservatism on the quality of profit, (2) the effect of investment opportunity set on earnings quality, (3) managerial ownership moderate conservatism on earnings quality, (4) managerial ownership moderate investment opportunity set on earnings quality. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange period of observation 2013-2015. The number of samples of this study is 63 companies with 189 observational data. Sampling in this research using non probability method with purposive sampling technique that is by using certain criterion for sample selection. Data analysis techniques in this study using moderated regression analysis (MRA). The results showed that conservatism had a positive effect on earnings quality, while investment opportunity set had negative effect to earnings quality. This study is unable to prove managerial ownership moderate the influence of conservatism and investment opportunity set on earnings quality  Keywords : conservatism, investment opportunity set, earnings quality, managerial ownership